2022
DOI: 10.1177/14644207221110783
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of warm incremental sheet forming process on magnesium AZ31 and aluminium 6061 alloy

Abstract: Aerospace, automobile and biomedical sector focuses on innovative rapid manufacturing processes, which can enable product customization, reduction in cost and manufacturing lead time. Aerospace, automobile and biomedical industries mostly use magnesium AZ31 and aluminium 6061 alloy materials for manufacturing of products because of their lower elastic modulus, excellent corrosion and fatigue resistance. The conventional sheet metal forming processes often require additional tools like punch and die and would n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The same trend was observed for spring back as well. Recently, Mohanraj et al [33] performed WISF on magnesium AZ31 and aluminum 6061 alloys and achieved better formability and an exact shape at 300 • C.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was observed for spring back as well. Recently, Mohanraj et al [33] performed WISF on magnesium AZ31 and aluminum 6061 alloys and achieved better formability and an exact shape at 300 • C.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the forming behaviour under different processes like stretch forming, 16,17 deep drawing 18,19 and incremental sheet metal forming 20,21 is essential as the material undergoes different deformation modes under these processes. Especially, the investigation of the deep drawing behaviour of CP Ti is of much interest for the fabrication of sheet metal components.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to prevent the formation of bump structures due to delamination during SPIF of laminated sheets by making the right tool path selections. Mohanraj et al 21 experimentally investigated the effects of process parameters on warm incremental sheet metal forming of aluminum 6061 and magnesium AZ31 alloy materials using electric heating technique. From the experimental findings, the authors concluded that sheet metal components made of AZ31 and AA6061 alloys could be formed with the greatest degree of formability and thickness reduction while exhibiting the least amount of geometrical deviation when using 50° wall angle and 300°C temperature and 0.1 mm incremental depth.…”
Section: Introductionmentioning
confidence: 99%